A MULTIDISCIPLINARY SPORTS MEDICINE PERFORMANCE MODEL IN ELITE WOMENS INTERNATIONAL SOCCER. Issue 4 (1st February 2017) - Boyce, Stephen; Davies, Oliver; McKenna, Michael; White, Andrew; Dixon, Mark; Elliott, Niall
Abstract : Background: The traditional sports medicine "backroom" team in elite women's international soccer was comprised of a doctor and physiotherapist(s). Objective: To introduce a multidisciplinary sports medicine performance model into elite women's international soccer and assess its impact. Design: Prospective observational study. Setting: Scotland women's soccer national squad. Participants: Elite women international soccer players. Interventions: Introducing a sports science physiologist and strength and conditioning coach into the sports medicine team. Main Outcome Measurements: To monitor objective measurements and subjective health and wellbeing data on a daily basis at international squad gatherings. Results: All players reported to a health and wellbeing assessment in the medical area each morning. The following data was collected: Illness and injury surveillance, Urine hydration status, Body weight, Resting heart rate, Menstrual cycle, Physical objective tests (Sit and reach distance, Knee to wall distance, Thomas test, Counter movement jump height), Health and Wellbeing data (Fatigue status, Stress, Sleep quality, Motivation). The performance indicators were discussed amongst the sports medicine team and concerns regarding a player's health and fitness relayed to the coaching staff. Conclusions: Changing a traditional approach to performance and incorporating other professionals skills by working in partnership in a new sports medicine performance model provided an efficient method of determining player's health, wellbeing and fitness on a daily basis allowing discussion within the sports medicine team with any concerns relayed to the coaching staff over performance indicators.